Direct Measurement of 226Ra from g-Ray Spectroscopy Using an Interference Correction - Ji, Young-Yong; Ho Chung, Kun; Lim, Jong-Myoung; Jang, Mee; Kim, Chang-Jong; Ja Kang, Mun; Choi, Geun-Sik (Asian Journal of Chemistry, 2014)
There are several methods used to determine the concentration of 235U, 238U and 226Ra in natural occurring radioactive materials samples through a radiochemical analysis using an alpha spectrometer, a mass spectrometer and a liquid scintillation counter. However, a g-ray spectrometer still has an effect on the assessment of radioactive concentrations for these nuclides and their progenies. In this study, a direct measurement with the interference correction and an indirect measurement, which means the identification of 226Ra indicators such as 214Pb and 214Bi after the secular equilibrium in the natural occurring radioactive material sample, were introduced and compared for analyzing 235U and 226Ra. Their results were also compared with those from the inductively coupled plasma mass spectrometer (ICP-MS) for the same samples and the optimum method for direct measurement of 226Ra was then selected as considering its accuracy and uncertainty. Finally, the results of 226Ra were used to evaluate the radioactive disequilibrium in raw materials and by-products.